Interplay of T Helper 17 Cells with CD4+CD25high FOXP3+ Tregs in Regulation of Allergic Asthma in Pediatric Patients - Amit Agarwal; Meenu Singh; B. P. Chatterjee; Anil Chauhan; Anuradha Chakraborti (Hindawi Limited, 2014)
Background. There is evidence that Tregs are important to prevent allergic diseases like asthma but limited literature exists on role of TH17 cells in allergic diseases. Methods. Fifty children with asthma and respiratory allergy (study group) and twenty healthy children (control group) were recruited in this study. Total IgE levels and pulmonary function tests were assessed. The expression of Tregs and cytokines was determined by flow cytometry. Results. The average level of total IgE in study group (316.8 ± 189.8 IU/mL) was significantly higher than controls (50 ± 17.5 IU/mL, P<0.0001). The frequency of TH17 cells and culture supernatant level of IL-17 in study group (12.09 ± 8.67 pg/mL) was significantly higher than control group (2.01 ± 1.27 pg/mL, P<0.001). Alternatively, the frequency of FOXP3 level was significantly lower in study group [(49.00 ± 13.47)%] than in control group [(95.91 ± 2.63)%] and CD4+CD25+FOXP3+ to CD4+CD25+ ratio was also significantly decreased in study group [(6.33 ± 2.18)%] compared to control group [(38.61 ± 11.04)%]. The total serum IgE level is negatively correlated with FOXP3 level (r=-0.5273, P<0.0001). The FOXP3 expression is negatively correlated with the IL-17 levels (r=-0.5631, P<0.0001) and IL-4 levels (r=-0.2836, P=0.0460). Conclusions. Imbalance in TH17/Tregs, elevated IL-17, and IL-4 response and downregulation of FOXP3 were associated with allergic asthma.